Safety, efficacy, and impact on gut microbial ecology of a Bifidobacterium longum subspecies infantis LMG11588 supplementation in healthy term infants: a randomized, double-blind, controlled trial in the Philippines - Capeding, Maria Rosario Z.; Phee, Loudhie Cyd M.; Ming, Chang; Noti, Mario; Vidal, Karine; Le Carrou, Gilles; Frézal, A.; Moll, Janne Marie; Vogt, Josef Korbinian; Myers, Pernille Neve; Nielsen, Bjørn Henrik; Boulangé, Claire L.; et al. (Frontiers in Nutrition, 2023)
Introduction: Bifidobacterium longum subspecies infantis (B. infantis) may play a key role in infant gut development. This trial evaluated safety, tolerability, and efficacy of B. infantis LMG11588 supplementation. Methods: This randomized, placebo-controlled, double-blind study conducted in the Philippines included healthy breastfed and/or formula-fed infants (14-21 days old) randomized for 8 weeks to a control group (CG; n=77), or any of two B. infantis experimental groups (EGs): low (Lo-EG; 1*10^8 CFU/day; n=75) or high dose (Hi-EG; 1.8*10^10 CFU/day; n=76). Primary endpoint was weight gain; secondary endpoints included stooling patterns, gastrointestinal symptoms, adverse events, fecal microbiome, biomarkers, pH, and organic acids. Results: Non-inferiority in weight gain was demonstrated for Hi-EG and Lo-EG vs. CG. Overall, probiotic supplementation promoted mushy-soft stools, fewer regurgitation episodes, and increased fecal acetate production, which was more pronounced in the exclusively breastfed infants (EBF) and positively correlated with B. infantis abundance. In EBF, fecal proinflammatory cytokines (IL-1 beta, IL-8) were reduced. Strain-level metagenomic analysis allowed attributing the increased abundance of B. infantis in EGs versus CG, to LMG11588 probiotic colonization. Colonization by autochthonous B. infantis strains was similar between groups. Discussion: B. infantis LMG11588 supplementation was associated with normal infant growth, was safe and well-tolerated and promoted a Bifidobacterium-rich microbiota driven by B. infantis LMG11588 colonization without disturbing the natural dispersal of autochthonous B. infantis strains. In EBF, supplementation stimulated microbial metabolic activity and beneficially modulated enteric inflammation.